Comparison of speed loop control methods for IPM motor in electric vehicles - Thi Hoai Thu Anh, An; Nhu, Tran Van; Hieu, Tran Trong (Institute of Advanced Engineering and Science, 2025)
With its outstanding features, such as high efficiency and torque-producing capability compared with the induction motor, the interior permanent magnet synchronous motor (IPMSM) has been increasingly researched and used for electric vehicles. The speed control strategy for both low and high speeds of the IPMSM is studied in conjunction with controllers based on the field oriented control (FOC) structure to ensure accurate and stable system response under various operating conditions. This paper focuses on three control methods: sliding mode control (SMC), backstepping (BSP), and proportional integral (PI) for the speed loop to enhance system stability. Coupled with the presence of load disturbances, environmental disturbances, and uncertainties in parameters, comparisons and observations regarding the three methods can be made to conclude system stability and performance. Finally, simulation results on MATLAB/Simulink software confirm the effectiveness and validity of the proposed speed controllers.